Ular Welang, Bungarus fasciatus (Schneider, 1801), di Lereng Selatan Gunung Merapi, Daerah Istimewa Yogyakarta - Donan Satria Yudha; Rury Eprilurahman; M. Fahrul Hilmi; Iman Akbar Muhtianda; Aisyah Arimbi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2013)
There are three known kraits species of the Genus Bungarus (Elapidae) inhabit Java Island, Indonesia. Two species out of the three species, i.e., Bungarus candidus (Malayan kraits) and Bungarus fasciatus (Banded kraits) are commonly found in Daerah Istimewa Yogyakarta (DIY) Province. However, a longterm  research about herpetofauna diversity in the Southern slope of Mount Merapi since 2006 until 2011 shows no species records from genus Bungarus. A nocturnal survey on April 28th, 2012 was administerd around the Kaliurang recreational area. We found snake which was suggested belong to the genus Bungarus. Detailed identification showed that this snake was Bungarus fasciatus or banded kraits snake. This finding provide the new record of genus Bungarus in Southern slope of Merapi especially since the periodical research of herpetofauna diversity which was started in 2006. To complete the data, it needs intensive research to know the distribution and species abundance of Bungarus fasciatus in Southern slope of Mount Merapi.